Tax Relief in Disaster Situations - Heidi B. Copeland; Jorge Ruiz-Menjivar (EDIS)
This 1-page document provides general information regarding disaster assistance and links to online resources for taxpayers affected by a federally declared disaster. Written by Jorge Ruiz-Menjivar and Heidi Copeland, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised September 2020. https://edis.ifas.ufl.edu/fm259